Climate change and its effect on some physiological processes of the agricultural plants : A literature review - Cong, Doan Van (GEORGIKON FOR AGRICULTURE, 2016)
Climate change is one of the most important issues because of its impacts the human being. Greenhouse gases (GHGs), among others, including carbon dioxide (CO2), nitrogen dioxide (NO2), and methane (CH4) are the main components causing global warming. Different kinds of sources exist; the two most important ones are industrial emission and agricultural activities. Increasing Earth’s surface temperature, changing precipitation and losing coastal land due to sea level increase are the phenomenon of climate change that can be easily identified every day. Agricultural activities are strongly associated with the climatic conditions, because most of the plant’s physiological processes such as photosynthesis, stomatal resistance, canopy temperature and flowering time are affected by environmental factors as light, temperature and CO2 concentration. Therefore, understanding of these phenomena and its effects on agricultural activities will assist us in finding good solutions for better adaptation to climate change.